The Challenges of the Digital Era to the Quality of Education in Sociology (Can the Logos Be Attractive?) - Rakadzhijska, Temenuga (Research Papers, 2018)
The digital era puts humanity ahead of new challenges. They affect every sphere of human activity, including education. The article attempts to specify these challenges in terms of changing social relationships. Their sociological reflection is sought and also the need from new practices and standards in sociology education. JEL: I290; Z100